Epidemiological study of clinical signs and symptoms of mercury poisoning in fish consumers residing in five villages along Thane Creek and Ulhas River Estuary near Mumbai, India - Menon, Jayashree S. (Our Nature, 2017)
The fish of Thane Creek and Ulhas River Estuary are contaminated with mercury. The traditional fishing folks residing along these water sources consume large amounts of these fish for their sustenance, therefore, being vulnerable to mercury poisoning. A survey on the clinical signs and symptoms of mercury poisoning was carried out in Wehele, Alimgarh and Diwe-Kewni along Ulhas River Estuary and Vittawa and Airoli along Thane creek. Fortunately, no alarming signals of mercury poisoning could be detected in these populations. Genetic make-up and/or use of onion and garlic in the fish preparations could be the probable detoxifying factors in these populations. However, these populations being vulnerable to mercury poisoning, continuous monitoring is recommended in these areas. This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.